2022
DOI: 10.3168/jds.2022-22051
|View full text |Cite
|
Sign up to set email alerts
|

Veterinarian perceptions on the care of surplus dairy calves

Abstract: Both male and female calves that are not required in the dairy herd sometimes receive inadequate care on dairy farms. Veterinarians work with farmers to improve animal care, and farmers often view veterinarians as trusted advisors; however, little is known about the attitudes of veterinarians on surplus calves. This study investigated the perspectives of Canadian cattle veterinarians on the care and management of surplus calves, as well as how they view their role in improving care. We conducted 10 focus group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…That farmers emphasised the importance of colostrum management in mitigating calf diseases on dairy farms has been previously reported (Sumner et al 2018 ). However, other focus group work done in our research group reported that veterinarians are frequently sceptical as to whether colostrum management on dairy farms is carried out according to best practices (Sumner & von Keyserlingk 2018 ; Hendricks et al 2022 ).…”
Section: Resultsmentioning
confidence: 93%
“…That farmers emphasised the importance of colostrum management in mitigating calf diseases on dairy farms has been previously reported (Sumner et al 2018 ). However, other focus group work done in our research group reported that veterinarians are frequently sceptical as to whether colostrum management on dairy farms is carried out according to best practices (Sumner & von Keyserlingk 2018 ; Hendricks et al 2022 ).…”
Section: Resultsmentioning
confidence: 93%
“…Recent work indicates that there may be growing acceptance by veterinarians working within the cattle industries that public concern in this area should not be discounted. For example, Hendricks et al ( 2022b ) interviewed Canadian veterinarians about the fate of surplus calves and reported that they felt that they had a role in educating their clients as to the changing societal norms around animal care.…”
Section: Resultsmentioning
confidence: 99%
“…They decide when or how to care for an animal and when to end care. Moreover, human owners have the final say in treatment, even when their choice is subpar, such as when they opt for euthanasia against the veterinarian's expert advice (Hendricks, Weary, & von Keyserlingk, 2022).…”
Section: An Integrative Overview Across Typesmentioning
confidence: 99%